Focused array analysis of diabetic skin wound. - Ling, Wei Yin. (2009)
Impaired wound healing in diabetic patients is a predisposing condition leading to high rate of amputations. Dysregulation of growth factors and cytokines involved in angiogenesis is the underlying reason for impaired healing. To understand the interplay among these players behind angiogenesis and discover possible therapeutic targets, a focused array approach employing real-time quantitative PCR technique was used to unravel the differential gene molecular profiles in the healing of chronic diabetic mice wounds compared to that of normal wounds. In vivo analyses using wildtype (+/+) and diabetic (ob/ob) mice wounds revealed many angiogenic factors and inflammatory mediators with altered gene expression patterns and levels leading to the chronic inflamed state of diabetic wounds. These molecular signatures, represented by heatmaps, serve as potential platforms for clinicians to diagnose chronic diabetic wounds. Literature mining based on the altered expression profiles generated a molecular network allowing us to derive appropriate therapeutic interventions. Herein, novel genes were identified to be prospective targets in the treatment of diabetic wounds. In particular, inflammatory mediators like TNFα, GM-CSF and IL-10 and angiogenic factor like VEGF may be manipulated to reverse the aberrant healing process and consequently, alleviate the impaired wound healing in diabetic patients.